Learning to read in a digital world - Barzillai, Mirit; Thomson, Jennifer M.; Schroeder, Sascha; Broek, Paulus Willem van den, 1955- (Studies in written language and literacy, 2018)
"With digital screens becoming increasingly ubiquitous in the lives of children, from their homes to their classrooms, understanding the influence of these technologies on the ways children read takes on great importance. The aim of this edited volume is to examine how advances in technology are shaping children's reading skills and development. The chapters in this volume explore the influence of various aspects of digital texts, the child's cognitive and motivational skills, and the child's environment on reading development in digital contexts. Each chapter draws upon the expertise of scientists and researchers across countries and disciplines to review what is currently known about the influence of technology on reading, how it is studied, and to offer new insights and research directions based on recent work"--